Neuropharmacological screening of Ficus Carica Linn; Fruit for Anxiolytic and Antidepressant Activity (Bangladesh Journal of Medical Science, 2018)
Background: Rutin and polyphenol which are present in ficus carica linn are responsible for anti-depressant and anxiolytics effect.Aims: We have conducted the study to evaluate the anti depressant and anxiolytic effect of ficuscaricalinn on mice and compare its effect with well known prescribed anti depressant and anxiolytic drug alprazolam.Methods: Three groups of mice were marked as Control, Reference and Test. Each group comprise of 5 mice. Control group was on normal diet. Reference group was feeded alprazolam at a dose of 0.5mg/60kg while test group were provided two different dilution of ficuscaricalinn, one dilution is 250mg/ kg/100ml of water and second dilution is 500mg/kg/100ml of water. We used Light/dark box method and Elevated plus maze method to evaluate the anxiolytic effect of ficus carica linn. To determine the anti-depressant effect of ficus carica linn.Results: we was used one method that is Head Dip Method. Results were collected and observed readings and data were clearly indicating the great and pronounced anti depressant and anxiolytic effect of ficus carica linn at a dose of 500mg/kg compare with a widely prescribed drug alprazolam for its anti-depressant and anxiolytic effect.Ficus carica is well known for its numerous biological activities also found to be one of excellent distressing agent. Stress provoking several disorders could be limit by the use of ficus carica fruit in doses 250mg/kg and 500mg/kg. Ficus carica linn as a natural product may prove better therapeutic agent if more study is conducted on it.Conclusion: As this study is confined to the mice, there’s much possibilities to have similar effect in humans but require more work on it.Bangladesh Journal of Medical Science Vol.17(4) 2018 p.606-611